Sports in the Moscow Palace of Young Pioneers - Shkedova, Natalia (project baikal, 2017)
The article reviews two projects of the Moscow Palace of Young Pioneers on Vorobyovy Gory: a unique project realized in 1962, and a contemporary project of the development of the territory of the Palace of Young Pioneers worked out by an interdisciplinary team in 2015. It is shown how legacy of the past becomes a unique opportunity of the future.
Keywords: sports; children’s supplementary education and development; permeability; multifunctionality; space transformation